2017
DOI: 10.13075/ijomeh.1896.00818
|View full text |Cite
|
Sign up to set email alerts
|

The association between body-built and injury occurrence in pre-professional ballet dancers – Separated analysis for the injured body-locations

Abstract: Objectives: This study has aimed at identifying prevalence of injury-occurrence in 24 pre-professional-ballet-dancers (females, 16-18 years of age), and identifying the associations between the body-built and prevalence of injuries. Material and Methods: The sample of variables included: body mass, body height, and 3 somatotype characteristics (mesomorph, ectomorph and endomorph) and data on injuries over the preceding year. Results: Dancers were mostly ectomorphic-mesomorph (endomorphy: 2.6±0.54, mesomorphy: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 22 publications
1
33
1
1
Order By: Relevance
“…Overuse injuries were related to less bilateral plié ( P < 0.001) and decreased left ankle DF (P < 0.05) Negus et al [ 30 ] N = 29 (24 females) Student dancers Aged 15–22 years • Hip external rotation ROM in supine (passive and active) • Functional turnout in standing • Active external rotation lag • Compensated turnout (CT) (= static functional turnout angle (standing in 1st, 5th right,5th left)—total active hip external rotation (supine)) • Static-dynamic turnout (SDTD) (= standing in 1st,5th right,5th left)—dynamic functional turnout angle (landing in same 3 positions after jumping) ‘Any pain, discomfort or other musculoskeletal problem, which required modification of, or time away from, dance training, examinations, or performance’ Categorised as traumatic and non-traumatic Self-reported VAS scale used to self-report severity and perceived impact of injury Number of non-traumatic injuries was positively correlated with 6 of 7 derived turnout variables; compensated turnout in all 3 positions and static dynamic turnout difference in all 3 positions ( r = 0.39–0.55, P < 0.039). Severity of non-traumatic injuries was positively correlated with 3 of 7 derived turnout variables: static-dynamic turnout difference in all positions (rho = 0.38–0.47, P < 0.043) Non-traumatic injuries— CT first, right fifth, left fifth, SDTD first, SDTD right fifth, SDTD left fifth correlated with number of injuries SDTD first, SDTD right fifth, SDTD left fifth correlated with injury severity No correlations to traumatic injury Zaletel et al [ 31 ] N = 24 females Ballet high school students 16–18 years 165.3 ± 5.7 cm 55.2 ± 5.4 kg • Body mass • Height • Skinfolds: triceps, subscapular, calf, suprailiac ‘Any physical complaint sustained as a result of performance or training, irrespective of the need for medical attention or time lost from activity’ Self-reported by questionnaire Increased likelihood of ankle injuries for endomorphs (OR = 1.887) Increased likelihood of foot injury for ectomorph (OR = 1.719) Toe injuries more prevalent in dancers with higher body mass (OR = 1.688) Bhakay et al [ 32 ] N = 22 females Professional ballet dancers attending Indian dance schools 14–30 years • External hip rotation • Functional turnout • Compensated turnout ‘Any pain or dysfunction of the lower extremities that impacted the dancers’ ability to practice or perform’ Self-reported Relationship between total hip external rotation ( P = 0.0137), functional turnout ( P = 0.0176) and compensated turnout ( P = 0.0002) and injury Wong et al [ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overuse injuries were related to less bilateral plié ( P < 0.001) and decreased left ankle DF (P < 0.05) Negus et al [ 30 ] N = 29 (24 females) Student dancers Aged 15–22 years • Hip external rotation ROM in supine (passive and active) • Functional turnout in standing • Active external rotation lag • Compensated turnout (CT) (= static functional turnout angle (standing in 1st, 5th right,5th left)—total active hip external rotation (supine)) • Static-dynamic turnout (SDTD) (= standing in 1st,5th right,5th left)—dynamic functional turnout angle (landing in same 3 positions after jumping) ‘Any pain, discomfort or other musculoskeletal problem, which required modification of, or time away from, dance training, examinations, or performance’ Categorised as traumatic and non-traumatic Self-reported VAS scale used to self-report severity and perceived impact of injury Number of non-traumatic injuries was positively correlated with 6 of 7 derived turnout variables; compensated turnout in all 3 positions and static dynamic turnout difference in all 3 positions ( r = 0.39–0.55, P < 0.039). Severity of non-traumatic injuries was positively correlated with 3 of 7 derived turnout variables: static-dynamic turnout difference in all positions (rho = 0.38–0.47, P < 0.043) Non-traumatic injuries— CT first, right fifth, left fifth, SDTD first, SDTD right fifth, SDTD left fifth correlated with number of injuries SDTD first, SDTD right fifth, SDTD left fifth correlated with injury severity No correlations to traumatic injury Zaletel et al [ 31 ] N = 24 females Ballet high school students 16–18 years 165.3 ± 5.7 cm 55.2 ± 5.4 kg • Body mass • Height • Skinfolds: triceps, subscapular, calf, suprailiac ‘Any physical complaint sustained as a result of performance or training, irrespective of the need for medical attention or time lost from activity’ Self-reported by questionnaire Increased likelihood of ankle injuries for endomorphs (OR = 1.887) Increased likelihood of foot injury for ectomorph (OR = 1.719) Toe injuries more prevalent in dancers with higher body mass (OR = 1.688) Bhakay et al [ 32 ] N = 22 females Professional ballet dancers attending Indian dance schools 14–30 years • External hip rotation • Functional turnout • Compensated turnout ‘Any pain or dysfunction of the lower extremities that impacted the dancers’ ability to practice or perform’ Self-reported Relationship between total hip external rotation ( P = 0.0137), functional turnout ( P = 0.0176) and compensated turnout ( P = 0.0002) and injury Wong et al [ …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies included dancers across this age range [ 5 , 28 , 30 32 , 41 , 56 , 57 ], and four studies did not report the age [ 33 , 37 , 42 , 51 ]. Gender reporting revealed that 13 studies included females only [ 26 , 31 , 32 , 34 , 39 , 40 , 43 , 44 , 49 , 52 , 60 , 63 , 64 ], 28 studies were mixed [ 5 , 24 , 27 30 , 35 38 , 41 , 42 , 45 – 48 , 50 , 51 , 53 59 , 61 , 62 , 65 ] and in one study, the gender was unclear [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were excluded because the definition of “groin problems” or “complaints” rather than “pain” was used 16,50,51 . Eleven studies that reported injury rather than pain were excluded 52–62 . One study that reported hip and knee pain combined was also excluded 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Estos parámetros muestran propiedades para distinguir un rango de valores que, a pesar de encontrarse saludables, no son óptimos para ciertos deportes y establecen un nivel prototípico empírico basal. Además, los parámetros de composición corporal que están representados en un somatotipo, han mostrado un valor predictivo en la probabilidad de presentar una lesión relacionada con el entrenamiento 25. Los modelos de regresión lineal mostraron un comportamiento similar en todos los grupos, lo que revela que la mesomorfia basal y la endomorfia predicen los resultados del entrenamiento en los cambios de la mesomorfia, lo cual no aplica en la endomorfia y la ectomorfia, donde sólo se encuentran los valores basales como predictivos para el cambio final de la misma variable; este hallazgo podría tenerse en cuenta para enfocarse en la detección de personal con una condición física deficiente mediante el somatotipo y el refuerzo de su programa de entrenamiento.…”
unclassified